The synthesis and characterisations of porous thioamide- sulfonated-modified poly (acrylonitrile-co- divinylbenzene-80) as potential sorbent to capture polar analytes - Ismail, Farhana Syakirah (2019)
Pharmaceuticals contain biologically active components that can pollute watercourses as a result of excretion from individuals and the uncontrolled release of residues from chemical plants. Pharmaceutical residues can persist at low concentrations in the environment, and thus may be potentially harmful to aquatic animals and humans. The control and monitoring of such residues are therefore of prime interest by, for example, solid-phase extraction using solid sorbents to purify and preconcentrate the residues prior to their chemical analysis. In the present work, poly(acrylonitrile-co-divinylbenzene-80) (poly(AN-co-DVB-80)) sorbents were synthesised by varying the comonomer feed ratios under precipitation polymerisation conditions to deliver a family of porous polymer microspheres. Acrylonitrile confers polar character onto the sorbents, and the acrylonitrile-derived nitrile groups can be chemically transformed via polymer-analogous reactions into thioamide and sulphonyl functional groups which make the sorbents even more suitable for the capture of polar analytes, including pharmaceuticals. In the present study, the Fourier transform infrared (FTIR) spectroscopy results confirmed the chemical modification of poly(AN-co-DVB-80) (P33) to form thioamide-modified poly(AN-co-DVB-80) (TP33) and sulphonation thioamide-HSO3-modified poly(AN-co-DVB-80) (TP33-HSO3) due to the presence of strong peaks at 1050 cm-1 and 1154.47 cm-1 that were assigned to the stretching vibrations of C=S group and SO3H group in TP33 and TP33-HSO3, respectively. The Bruneaur-Emmett-Teller (BET) data demonstrated that the specific surface area of P33 had decreased significantly from 565.0 m2g-1 (P33) to 330.0 m2g-1 (TP33) and 5.9 m2g-1 (TP33-HSO3) after the chemical modifications were carried out with thiourea and sulphuric acid, respectively. The scanning electron microscopy (SEM) analysis proved that the morphologies structure of the copolymers was retained after chemical modification and sulphonation. The TP33 had 4.3% of sulphur content due to the chemical modification of the P33 with thiourea, while the amount of sulphur in TP33-HSO3 was the highest (6.5%) due to the sulphonation with sulphuric acid. The performance of the porous thioamide-sulphonated (TP33-HSO3) sorbents was demonstrated via the dispersion-solid phase extraction of mefenamic acid (MA), salicylic acid (SA), and diclofenac (DCF) from aqueous medium. It was found that the highly functionalised TP33-HSO3 has better extraction compared to the TP33 despite its low specific surface area. Meanwhile, the extraction of pharmaceuticals by using TP33 was better compared to the extraction by using P33, although the specific surface area (SSA) of TP33 is 330.0 m2g-1 and SSA of P33 is 565.0 m2g1. This finding showed that in addition to the role of SSA that influenced the extraction process; the presence of active functionalised groups also contributed to the extraction efficiency of the sorbents to extract polar pharmaceuticals. It was found that the maximum extraction for TP33 for MA, SA and DCF were 93.88 mg.g1 (78.23%), 80.07 mg.g-1 (66.72%) and 70.70 mg.g-1 (58.91%), respectively, while maximum extraction for TP33-HSO3 were 96.88 mg.g-1 (80.73%), 97.15 mg.g-1 (80.96%) and 69.51 mg.g-1 (57.93%), respectively.